Mapping the corporate governance scholarship: Current state and future directions. (19th April 2022) - Pandey, Nitesh; Andres, Christian; Kumar, Satish
Abstract: Research Question/Issues: We conduct a comprehensive analysis of all scholarly publications in the field of corporate governance (CG) since the Enron scandal of 2001. Using bibliometric methods, we identify prominent themes that have served as the foundation of CG research, prominent topics in the field along with their temporal developments, and recent trends in CG research. In addition, we identify the authors and journals that have had the biggest impact in the field. Research Findings/Insights: We document that the number of annual publications in CG has increased by a factor of eight since the early 2000s, with research articles being published in a wide variety of general interest journals, as well as in outlets specialized in the field of CG. We identify six research themes as the foundation of CG research: the theoretical foundations of CG, ownership, CG mechanisms and firm outcomes, disclosures, the board of directors, and family firms. We further find 19 major bibliographic keyword clusters that have been explored by researchers in the past 20 years. Research on corporate social responsibility (CSR) and sustainability, governance mechanisms, control mechanisms and disclosures, board diversity, CG in family firms, and CG in the Chinese context are the most dynamic areas of research in recent years. Theoretical/Academic Implications: We systematically analyze the literature on CG and outline theoretical foundations, structuring academic contributions by keyword clusters. Links between keyword clusters as well as the most dynamic research areas are identified. The analysis provides guidance for researchers regarding suitable outlets for the different thematic clusters and helps as a basis to identify research opportunities. Practitioner/Policy Implications: We document growing research interest in the field of CSR and sustainability. The growing body of literature in these areas can inform CG and CSR policies in the future. Our comprehensive bibliographic analysis provides an overview of CG research themes across research disciplines and streams of the literature.